AGAMA: DARI ISOLASI KE PRO-EKSISTENSI Refleksi Teologis-Dialogal Hidup Beriman - Armada Riyanto; Sri Wismoady Wahono (Studia Philosophica et Theologica, 2002)
What is the true sense of religion today? Prof. Wismoady Wahono PhD, one of the Indonesian leading theologians who just passed away to God’s embracing hands a few days before this publication, traces succinctly the sense of religion. He also suggests what would be the proper meaning of religion that should be cultivated in the current situation of Indonesia. Religion should not be a formal emblem of a person living in a society. It should lead him to cope any challenge of peaceful religious pro-existence especially in Indonesia. Armada Riyanto goes further to discuss the topic dealt with in the context of theology of pluralism. “Is there a basic Christian consensus theology today in spite of all our differences?” This is a typically question put forward by some theologians of pluralism. The sense of religious pro-existence is identical with that of living dialogically the Christian faith. This article consists of two main parts: tracing the meaning of living religion from isolation to pro-existence (in context of the Indonesian plurality) and theological discussion concerning “pro-existence” as not just living together peacefully but living the Christian faith embracing dialogically the differences (in context of the theological opinions of pluralism).